Jual Beli Di Bawah Tangan Terhadap Lahan Tempat Tinggal Transmigran Di Nagari Ranah Palabi Kecamatan Timpeh Kabupaten Dharmasraya Provinsi Sumatera Barat (Studi Pada Kantor Pertanahan Kabupaten Dharmasraya Provinsi Sumatera Barat) - Randa Iolanda Putra (Magister Kenotariatan, Universitas Jambi, 2020)
ABSTRACT The registration of land rights concerning title status, right subject, and right object is intended to guarantee legal certainty, legal protection, utility. According to UUPA, PP on Land Registration, and its derivation, it is one of the activities of safeguarding the land. The change in physical data and/or juridical data include the coverage of land registration data by transaction which can be proved with PPAT certificate. In reality, in Nagari Ranah Palabi, the transaction is done underhendedly on land title of the transmigrant settlement. The research problem is how about the cause, legal standing, and registration of the transfer of underhanded land transaction on the land right of transmigrant settlement. The research theories are the theory of legal certainty, theory of legal protection, and theory of utility. The research used juridical empirical and descriptive analytic method by analyzing primary data obtained directly from the people in the field. It wa done in Nagari Ranah Palabi, Timpeh Sub-district, Dharmasraya Regency, West Sumatera Province. The result of the reseacrh shows that underhanded transaction of the land of transmigrant settlement includes inexpensive cost, quick process, and easy to do. Legal standing of the transactiondoes not meet material requiment since it is not a certificate made before a PPAT even thougt it is allowed materially. Consequently, it cannot be registered in the Land Office and filing the claim to Court cannot do the proceeding because there is no dispute in it. Therefore, the request for the right for the land cannot be accepted by the Court. It is recommended thet legal counseling about legal consequense of underhanded transaction of the land for residence be provided. Accurate regulation for the people on land right for residence concerning formal preprequisite should be made – certificate made before a PPAT for registering land title transfer. Concerning the absence of the seller or ‘afwezigheid’ the buyer has the right to lodge a request the land right in the transmigrant land. Keywords : Land Transaction;Land for Residence;Transmigrant.